1999
DOI: 10.15288/jsa.1999.60.47
|View full text |Cite
|
Sign up to set email alerts
|

Beverage sales and drinking and driving: the role of on-premise drinking places.

Abstract: ABSTRACT. Objective: The relationships between on-premise drinking places, beverage specific alcohol sales and drinking and driving were examined in a time series cross-sectional study of place-of-last-drink data from Perth, Western Australia. Method: At arrest, 2,411 drinking drivers reported their last location of consumption. Tabulated by 57 premises over 4 years, the rates at which individual premises were referenced as the place-of-last-drink were taken to reflect the relative distributions of numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 13 publications
3
33
0
Order By: Relevance
“…Additionally, in their extensive research on drinking patterns and drunk driving, Gruenewald and colleagues (Gruenewald et al, 2002;Gruenewald, Millar, et al, 1996;Gruenewald, Mitchell, et al, 1996;Gruenewald et al, 1999;Treno et al, 2000) have found that frequency, amount, and location of drinking activities all interact to produce problematic outcomes. The data available in this study, which were derived from official police reports, did not allow a thorough examination of these routine drinking activities and how they were related to drunk driving over the period of time considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in their extensive research on drinking patterns and drunk driving, Gruenewald and colleagues (Gruenewald et al, 2002;Gruenewald, Millar, et al, 1996;Gruenewald, Mitchell, et al, 1996;Gruenewald et al, 1999;Treno et al, 2000) have found that frequency, amount, and location of drinking activities all interact to produce problematic outcomes. The data available in this study, which were derived from official police reports, did not allow a thorough examination of these routine drinking activities and how they were related to drunk driving over the period of time considered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gruenewald, Johnson, and Treno (2002) suggested that increased alcohol outlet density was related to higher rates of driving under the influence, potentially as a result of increased opportunities for consumption or changing patterns of use at these locations. In particular, Gruenewald, Stockwell, Beel, and Dyskin (1999) found rates of drunk driving to be positively related to alcohol sales from taverns/bars. Similarly, Gruenewald, Mitchell, et al (1996) found that greater levels of alcohol availability at restaurants were related to higher rates of alcohol-related accidents.…”
Section: Increasing Availability Of Alcohol and Riskmentioning
confidence: 98%
“…Restaurant density, and not bar density, has been shown to be associated with single-vehicle nighttime crashes (Gruenewald et al, 1996), driving after drinking (Gruenewald et al, 2002), and police reports of alcohol-related MVCs (Scribner et al, 1994). One study in Australia found an association between on-premise alcohol outlets and drinking and driving, but no association with MVCs (Gruenewald et al, 1999). Studies in the southern US found no association between alcohol outlets and alcohol-related MVCs (Stevenson et al, 1998) or MVC fatalities of 15-24-years-old young males (Kelleher et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This marketing would have had an impact in the NT and may well have complemented the LWA initiatives (e.g. [31]). In summary, there is evidence of substantial health benefits associated with the period following the introduction of LWA which were especially evident in relation to acute morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%